2000
DOI: 10.1007/s004410050005
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of Bcl-2 and Bax expression in relation to cell turnover and epithelial differentiation markers in the non-lactating human mammary gland epithelium

Abstract: The expression of the apoptosis-related proteins Bcl-2 and Bax was investigated by immunohistochemistry in the normal non-lactating human mammary gland in relation to cell proliferation and apoptosis. In order to characterize individual Bax/Bcl-2-immunoreactive cells, the epithelial markers cytokeratin 14 and 19 and the macrophage marker CD 68 were used. Secretory-like differentiation of epithelial cells was characterized by histochemistry and lectin staining of surface glycoconjugates. Cell proliferation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…It has been reported that ormal stem/precursor cells of various tissue origins express a high level of anti-apoptotic protein such as Bcl-2. 29,30 Taken together, an anti-apoptotic function might be a preferentially prepared mechanism in both normal and cancer stem cells. Next, we examined the tumorigenic potential and self-renewal ability of SP cells in NOD/SCID xenotransplant assay.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ormal stem/precursor cells of various tissue origins express a high level of anti-apoptotic protein such as Bcl-2. 29,30 Taken together, an anti-apoptotic function might be a preferentially prepared mechanism in both normal and cancer stem cells. Next, we examined the tumorigenic potential and self-renewal ability of SP cells in NOD/SCID xenotransplant assay.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro cell cultures, stem cells did not maintain the expression of p75NTR. Some cells inherited the selfrenewal capacity character of stem cells while other cells became committed or progenitor cells [32][33][34].…”
Section: Differentiation Of P75ntr Positive and Negative Cellsmentioning
confidence: 99%
“…This revealed that SP cells are more tolerant to apoptosis than non-SP cells. It has been reported that normal stem/precursor cells of various tissue origins express high levels of anti-apoptotic proteins such as Bcl-2 (22). Moreover, resistance of apoptosis has been suggested as a feature to enrich cancer stem cells from tumor specimens or tumor cell lines (23,24).…”
Section: Discussionmentioning
confidence: 99%